Response of upland rice to fungicide application - Prabhu, Anne Sitarama; Faria, Josias Corrêa de; Conto, Arnaldo José de (Pesquisa Agropecuaria Brasileira, 2014)
The yield response of upland rice (Oryza sativa L.) to the fungicide sprays was studied in three field experiments. One application of the fungicides tested (benomyl, blasticidin-S, edifenphos, kasugarnycin, benomyl + maneb, kasugamycin + captafol) increased yield as compared to untreated check. Differences were not evident either in neck blast control or in yield response between benomyl and kasugamycin sprays administered separately or in mixtures with maneb and captafol, respectively. Leaf and panicle blast were significantly reduced with one spray applied at heading or at flowering or two sprays in combination with any of these two. Among the fungicides utilized for the control of blast, edifonphos, benomyl, benomyl + maneb significantly reduced disease severity of narrow brown leaf spot. Economic analysis for yield indicated that in the areas with high risk of blast disease, the use of fungicide sprays separately constitutes the most adequate tecnology for disease management.
Keywords: chemical control; systemic fungicides; rice blast; Pyricularia oryzae; Oryza sativa